Land Use Effects on Soil Properties Derived from Various Parent Materials in Northern Iran - Ramezanpour, Hassan; Kahneh, Ehsan; Rasoli, Najmeh (Asian Journal of Chemistry, 2010)
This study investigated the five sites of mountain landforms consisting granite, phyllite, basaltic andesite (two sites) and andesitic basalt parent materials located in western part of Langaroud area (Lahijan). Each site had forest and tea with two plots including one representative profile and three locations around the profile for soil sampling (0-30 cm). The experimental design was completely randomized blocks as factorial and three replications. Results indicated that cation exchange capacity, pH,organic carbon, humic acid, exchangeable bases excluding Na (highest mean value in andesitic basalt), bacteria and fungal population were decreased in soil surface under tea cultivation. However, bulk density, exchangeable acidity and fulvic acid content(greater amount in granite)increased significantly. Furthermore, a negative correlation was found between pH values and fungal population (r = -0.616) as well as fulvic acid content (r = -0.874) but positive correlation with bacterial population. Higher carbon dioxide volatilization (respiration) was related to the forest of basaltic andesite. Fulvic acid content was increased much more than the fungal population by decreasing pH. Lower amount of clay and cation exchange capacity was related to granite whereas higher amounts of them related to andesitic basalt. Classification of these soils changed from typic hapludolls (andesitic basalt) and typic udorthents (granite) under forest to typic dystrudepts and typic hapludalfs under tea plantation, respectively. Deforestion and tea plantation under different parent material caused to decrease pH values and promote soil acidification, thus influences on declining the cation exchange capacity, nutrient supplying and soil organism population which is partly attributed to cultivation effect leading to lower organic matter as well as blocking the charge sites of the clay fraction by aluminum.